2007
DOI: 10.1101/gad.1528607
|View full text |Cite
|
Sign up to set email alerts
|

Two small regulatory RNAs establish opposing fates of a developmental axis

Abstract: Small RNAs are important regulators of gene expression. In maize, adaxial/abaxial (dorsoventral) leaf polarity is established by an abaxial gradient of microRNA166 (miR166), which spatially restricts the expression domain of class III homeodomain leucine zipper (HD-ZIPIII) transcription factors that specify adaxial/upper fate. Here, we show that leafbladeless1 encodes a key component in the trans-acting small interfering RNA (ta-siRNA) biogenesis pathway that acts on the adaxial side of developing leaves and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
271
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(282 citation statements)
references
References 32 publications
10
271
0
1
Order By: Relevance
“…Mutations in LEAF BLADELESS in maize, which encodes a homologue of SUPRESSOR of GENE SILENCING3 (SGS3) in Arabidopsis and is involved in the ta-siRNA production pathway, result in a similar seedling phenotype to sho1 and sho2, including defects in leaf polarity. This phenotype in maize is due to reduced expression of tasiR-ARF and increased accumulation of miR166 (28). In our microarray analysis, expression levels of some of the rice ETT/ARF genes were up-regulated in sho mutants (SI Table 2 and SI Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Mutations in LEAF BLADELESS in maize, which encodes a homologue of SUPRESSOR of GENE SILENCING3 (SGS3) in Arabidopsis and is involved in the ta-siRNA production pathway, result in a similar seedling phenotype to sho1 and sho2, including defects in leaf polarity. This phenotype in maize is due to reduced expression of tasiR-ARF and increased accumulation of miR166 (28). In our microarray analysis, expression levels of some of the rice ETT/ARF genes were up-regulated in sho mutants (SI Table 2 and SI Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The phenotype is caused by reduced expression of a ta-siRNA, tasiR-ARF, and overexpression of its targets, the ETT/ARF genes (25)(26)(27). tasiR-ARF and its target genes are conserved among Arabidopsis, maize, and rice (21,28). Mutations in LEAF BLADELESS in maize, which encodes a homologue of SUPRESSOR of GENE SILENCING3 (SGS3) in Arabidopsis and is involved in the ta-siRNA production pathway, result in a similar seedling phenotype to sho1 and sho2, including defects in leaf polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Among the sRNA loci down-regulated in wild type by drought stress (during the treatment or after the recovery), five were TAS3 loci (TAS3c-e, TAS3g, and TAS3i). Plant TAS3 genes are important regulators of leaf polarity and vegetative phase change (Peragine et al, 2004;Nogueira et al, 2007). Our finding that their expression is affected by long-term drought stress implies a connection between control of development and environmental conditions in maize leaves.…”
Section: Class II Transposons Are Frequent Sources Of Rmr6-dependentmentioning
confidence: 79%
“…In Arabidopsis, miR156 was proposed to regulate leaf cell number and size (Usami et al, 2009), and its induction under stress conditions was shown to maintain the plant in the juvenile state for a relatively longer period of time, which helps it withstand unfavorable environmental conditions (Cui et al, 2014;Stief et al, 2014). Another two miRNAs involved in the control of normal leaf growth and development were altered by the abiotic stress treatments miR166 and miR396 (Nogueira et al, 2007;Liu et al, 2009). MiR399 controls inorganic phosphate (Pi) homeostasis and its response to Pi is highly specific (Bari et al, 2006).…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Mmentioning
confidence: 99%
“…leaf primordia (Supplemental Figures 2B and 2C). According to a model proposed by Waites and Hudson (1995), the juxtaposition of adaxial (upper leaf) and abaxial (lower leaf) developmental fields generates a new leaf axis that promotes laminar outgrowth (Waites and Hudson, 1995;Timmermans et al, 1998;Nogueira et al, 2007;Candela et al, 2008;Douglas et al, 2010). This mechanism may have been co-opted to generate new growth axes in leaves with nonplanar morphologies, such as the maize prophyll (Johnston et al, 2010).…”
Section: Transcripts Implicated In Maize Leaf Initiation Are Redeploymentioning
confidence: 99%